2014
DOI: 10.1152/ajplung.00149.2014
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin upregulates local Ca2+signaling through ryanodine receptor-1 in airway smooth muscle cells

Abstract: . Calcineurin upregulates local Ca 2ϩ signaling through ryanodine receptor-1 in airway smooth muscle cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Moreover, CaN inhibitors (CsA and FK506) can modify RyR2 function, as Bandyopadhyay et al report they can reduce the frequency of spark calcium release [ 94 ]. This data is further supported by Savoia et al as they demonstrated in 2014 that application of a CaN autoinhibitory peptide reduces RyR2 calcium release frequency in airway smooth muscle cells [ 105 ].…”
Section: An Overview Of Calcineurin Function In Cardiac Physiologysupporting
confidence: 53%
“…Moreover, CaN inhibitors (CsA and FK506) can modify RyR2 function, as Bandyopadhyay et al report they can reduce the frequency of spark calcium release [ 94 ]. This data is further supported by Savoia et al as they demonstrated in 2014 that application of a CaN autoinhibitory peptide reduces RyR2 calcium release frequency in airway smooth muscle cells [ 105 ].…”
Section: An Overview Of Calcineurin Function In Cardiac Physiologysupporting
confidence: 53%
“…To determine whether activation of calcineurin is protective, we treated HEK293 cells with the metal ion Ni 2+ . Ni 2+ is a robust calmodulin-independent activator of calcineurin in vitro and in vivo [28, 48, 51]. Incubating HEK293 cells with Ni 2+ treatment resulted in clearance of pTDP-35 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in SMCs, some studies suggest that calcineurin does not modulate RyR function (922, 924, 925). In contrast, inhibition of calcineurin or its genetic knockout inhibits RyR1 function in murine airway smooth SMCs (1256). Thus, there may be regional or species differences in the role played by calcineurin in the modulation of SMC RyR function.…”
Section: Ryanodine Receptorsmentioning
confidence: 99%